Depression, Loneliness, and Suicide Risk among Latino College Students: A Test of a Psychosocial Interaction Model. Issue 1 (5th November 2018) - Chang, Edward C; Chang, Olivia D; Lucas, Abigael G; Li, Mingqi; Beavan, Collin B; Eisner, Rachel S; McManamon, Brianna M; Rodriguez, Natalie S; Katamanin, Olivia M; Bourke, Eliza C; de la Fuente, Amaia; Cardeñoso, Olga; et al.
Abstract: This study tested a psychosocial model of suicide risk in a sample of 156 Latino college students. Specifically, depression and loneliness were hypothesized to be important predictors of suicide risk (namely, hopelessness and suicidal behaviors) in Latino students. Results of conducting regression analyses indicated that, independent of age and gender, depression and loneliness were significant predictors of both indices of suicide risk examined in the present study. It is noteworthy that within the psychosocial predictor set of depression and loneliness, depression was consistently found to be nearly twice as strong a predictor than was loneliness. Moreover, we found evidence for a significant depression–loneliness interaction effect in predicting suicide risk. That is, the highest level of suicide risk was found among dysphoric Latino students who were also socially isolated. Our findings indicate that depression and loneliness are important factors to consider in understanding suicide risk among Latino college students.